The Role Of The Notary / Ppat In Implementing Credit Agreement With Mortgage Guarantee In The Regional Development Bank (BPD) Branch Of Slawi, Tegal Regency - Azhar Muzakir; Lathifah Hanim (Jurnal Akta, 2019)
The purpose of this study was to: 1) To know and analyze the role of the Notary / PPAT in deed and deed granting the credit agreement Mortgage in Regional Development Bank (BPD) Branch Slawi, Tegal. 2) To determine and analyze the role of the Notary / PPAT in manufacturing Manufacture Giving Credit Agreement and the Deed of Guarantee Rights at the National Land Agency (BPN) Tegal. 3) What are the obstacles and solutions Notary / PPAT in manufacturing Manufacture Giving Credit Agreement and the Deed of Guarantee Rights at the National Land Agency (BPN) Tegal. The data used in this study are primary data, secondary data and data tertiary to support the assessment, which was then analyzed qualitative descriptive method.Based on this study showed that the implementation of the provision of credit at PT. Bank Central Java Slawi, Tegal Branch conducted through five stages: stage of credit application, credit analysis, credit decision, the stage of manufacture of the credit agreement and the binding phase of credit with credit guarantees, loan agreements executed before Notary as a partner is obliged to check the validity of the guarantee Mortgage.Notary PPAT role in the loan agreement with collateral Mortgage provides legal certainty for the parties to the credit agreement.challenges and solutions faced by the Notary in conducting the manufacture of credit with security rights that is located on the non-disciplinary debtor Bank in the administration of the application for credit and the absence of the debtor or the bank on the signing of the Deed of Credit Agreement, the Deed of credit agreements already prepared draft by the banks (creditor) that it is unfair or detrimental to the customer (debtor), then often the banks (creditors) are not present in deed signatories.Keywords: The Role Of The Notary; Mortgage Guarantee; BPD.